Malicious code in the cloud - Damjanović, Dragan Z. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Abstract:Introduction/purpose: The paper analyzes the impact of malicious codes in the cloud. Malicious code is an unauthorized piece of code that violates the integrity of an application and infrastructure to cause certain effects, such as security breaches, spread of infections, and data infiltration from the computer with the help of malicious software - this is a simple form of data theft which can lead to disastrous consequences in all segments of society, especially when it comes to national security. To overcome this challenge, it is necessary to detect holes in the safety of cloud environments and repair them before the attackers use these vulnerabilities to bypass the integrated cloud infrastructure.Methods: Structural analysis, functional analysis, comparative analysis, synthesis.Results: There are many factors for collecting, comparing, and delivering intelligence data on cloud threats. Cloud applications are increasingly being targeted because their use to store and share data with mobile application hosting has been increased exponentially, enabling industrial automation and business information monitoring and procurement. In addition, billions of devices on the Internet use the cloud infrastructure as a background for processing and transmitting large data sets. Malicious code is easily distributed due to the ease of sharing documents and files via the cloud.Conclusion: As cloud technologies are taking a central place in the world of digital transformation, the threat to the cloud environment is expected to grow exponentially. This means that organizations need to ensure that the cyber security position of the cloud infrastructure they possess is robust and mature enough to combat all relevant security threats in order to minimize business risks. Understanding the nature of practical security controls and how they are assessed enables organizations to build a practical approach to security and privacy in the cloud.
Keywords: malicious code; cloud; malware; intelligence